Tax Effect on the Debt Denomination Decision of Multinational Projects - Liu, Y. Angela; Hsueh, L. Paul (Journal of International Business Studies, 1993)
In this paper, we examine the effect of differential corporate taxes on the debt denomination decision of U.S. multinational firms facing stochastic project cash flows and exchange rates. Assuming to international interest arbitrage opportunity, we show that U.S.-based multinational firms can maximize projects' expected NPVs by borrowing in the foreign currency, as long as the excess foreign tax credit can be fully utilized by the parent firm. Otherwise, multinational firms should borrow the weaker currency when a lower exchange rate is expected. The effect of differential tax rates on the risk of multinational projects with different debt-denomination alternatives also is examined.